Determination of temperature profile of the lithosphere between zero and 150 km penetration at Itagunmodi, Nigeria (2019)
In this work the temperature profile for the lithosphere was determined using data from radiogenic heat source and heat from other sources from 0 to 150 km depth was determined using a suitable mathematical expression. The temperature at the base of the lithosphere was given between 1200°C to 1600°C. The Fourier’s law was applied and the results showed that the profile range from 27.0°C to 1483.3°C. These results compared favourably well with existing literature values.